EVALUASI PENERAPAN TOTAL PRODUCTIVE MAINTENANCE PROSES THREADING COUPLING DI PT.CT. - Hindarwan, Rizky; Sirait, Ganda (Computer Science and Industrial Engineering, 2021)
PT.CT is a company that produces pipes for oil and gas (OCTG). Production machines used non-stop, from these conditions found equipment problems that were damaged such as machine sensors that did not respond to the program, clogged vacuum coolers, servo alarms sounded during the Threading Coupling process. The effects of some these defects have impact on the number of products that are not according with the planned time. The purpose of this study was to determine effectiveness of the machine using an approach to increase effectiveness using Total Productive Maintenance (TPM), while Overall Equipment Effectiveness (OEE) is a method used to measure the application of TPM and maintain equipment. In ideal conditions by eliminating 6 Big Loss then analyze the factors that affect the OEE value using the Fishbone Diagram (Ishikawa Diagram). The results showed that lowest OEE value obtained for the Mori Seiki CNC machine (SL25 B) was in November 2020 of 55.04% and the highest OEE value was obtained in August 2021 of 80.08% and this value had not yet reached the standard of 85 %. The proposed corrective action is to prioritize 2 out of 6 Major Losses such as rework loss and breakdown losses.